Geometric programming with mixed constraints - Ho, Carson (1975)
This paper contains a two-pronged approach for providing design engineers with a tool for solving a class of engineering optimization problems. The solution to the minimization and maximization of posynomials subjected to constraints of the form greater than or equal to (>), or mixed constraints is presented. A computer code for solving general geometric programming problems including those with mixed constraints is also presented and can be used by persons with only a cursory knowledge of geometric programming principles.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Quezon City.
Keywords: Geometric programming